Nitrogen Speciation in Silicate Melts at Mantle Conditions From Ab Initio Simulations. Issue 7 (29th March 2022) - Huang, D.; Brodholt, J.; Sossi, P.; Li, Y.; Murakami, M.
Abstract: Nitrogen (N) is a major ingredient of the atmosphere, but a trace component in the silicate Earth. Its initial inventory in these reservoirs during Earth's early differentiation requires knowledge of N speciation in magmas, for example, whether it outgasses as N2 or is sequestered in silicate melts as N 3−, which remains largely unconstrained over the entire mantle regime. Here we examine N species in anhydrous and hydrous pyrolitic melts at varying P‐T‐redox conditions by ab‐initio calculations, and find N‐N bonding under oxidizing conditions from ambient to lower mantle pressures. Under reducing conditions, N interacts with the silicate network or forms N‐H bonds, depending on the availability of hydrogen. Redox control of N speciation is demonstrated valid over a P‐T space encompassing probable magma ocean depths. Finally, if the Earth accreted from increasingly oxidized materials toward the end of its accretion, an N‐enriched secondary atmosphere might be produced and persist until later impacts. Plain Language Summary: Earth's atmosphere was likely formed by the spontaneous release of gases, either from magma oceans during early Earth's accretion, or through later volcanic activity. Although our present‐day atmosphere (attributed to the latter) is rich in nitrogen (N) (78%), whether this held true for the early Earth is unclear, and is determined by the species (that control the solubility) of nitrogen in the silicate melt (i.e., magma ocean). In this study, we investigate the speciation of nitrogen in silicate melts during Earth's accretion, and find that N is dissolved as N2 at oxidizing conditions, regardless of the magma ocean's depth, promoting nitrogen degassing from the magma ocean. Our results suggest that, if Earth's building blocks were sufficiently oxidized at later times, magma ocean outgassing might produce an N‐enriched atmosphere. Given the violent impact history on the early Earth, as inferred from that recorded on the surface of the Moon, atmospheric loss of N by impact erosion may provide an explanation for Earth's "missing" nitrogen. Key Points: Strong N‐N bonding found stable in magmas under oxidizing conditions over the entire mantle regime Redox conditions superimpose P and T in controlling nitrogen speciation (thus solubility) in deep magma oceans Nitrogen‐enriched secondary atmosphere might form if the Earth accreted from sufficiently oxidized materials